PENINGKATAN PENGETAHUAN TENTANG SETTING-UP MINI WORKSPACE VIDEO PEMBELAJARAN SAAT WFH - Atmojo, Heriyanto; Fuad, Ahmad (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
There is a new rhythm going on in my personal space as a teacher. On March 11, 2020, the World Health Organization (WHO) announced the status of a global pandemic for the 2019 corona virus disease (COVID-19), that the impact of the institution modifying home learning methods (WFH), of course, in practice as a teacher can be realized if supported by. the creativity factor. For me personally, I began to want to try to make the most of the advances in science and technology in teaching. The advancement of science and technology provides space for teachers to be able to create formulations in packaging learning videos. In order for productivity to remain good, of course, supported by an ideal mini workspace, so that it can still accommodate the learning needs of students at home.This type of research is carried out experimentally with student subjects. Data collection methods used are test, observation and interview methods.Ã‚Â Keyword: creativity, mini workspace setting-up